VIOLENCE AGAINST WOMEN. A PROBLEM OF LACK OF PENAL OR SOCIO-CULTURAL REGULATIONS? - Espinoza Bonifaz, Renzo (2019)
The research addresses the problem of violence against women. To do this, it defines genderbased violence in its various manifestations, details the evolution of international and national regulations on this matter and analyzes the official statistics provided by the competent state institutions. Later, it explains and sustains that the penal system does not resolve social conflicts, to later affirm and sustain that criminality is produced by the design of the social structure, and is learned in social interaction. Finally, it proposes the “government of crime” as an effective mechanism to reduce criminality against women to tolerable limits.